If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 156 + -5x = 31x + 20 Reorder the terms: 156 + -5x = 20 + 31x Solving 156 + -5x = 20 + 31x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-31x' to each side of the equation. 156 + -5x + -31x = 20 + 31x + -31x Combine like terms: -5x + -31x = -36x 156 + -36x = 20 + 31x + -31x Combine like terms: 31x + -31x = 0 156 + -36x = 20 + 0 156 + -36x = 20 Add '-156' to each side of the equation. 156 + -156 + -36x = 20 + -156 Combine like terms: 156 + -156 = 0 0 + -36x = 20 + -156 -36x = 20 + -156 Combine like terms: 20 + -156 = -136 -36x = -136 Divide each side by '-36'. x = 3.777777778 Simplifying x = 3.777777778
| .833333x-.2x+4=.7x | | 506-?=265 | | 7(2n-4)-5=-40+7n | | 4ln(x-4)=4 | | (p+3)x^2+(2p+3)x+p+5=0 | | -.4x-9=.9 | | 5x+14=-28x-9x | | 19-3e=2-5(e+1) | | (y^2+2)(4y+7)= | | 2r^2+3r-20=0 | | (3y-3)(y+3)= | | 5x-3=2+6x | | 7=2r+5r | | -129=-3(8-7p) | | (y+9)(y+6)= | | 5x+1=14x-73 | | 6d-2(d-2)=3(d-12) | | (x+7)(2x^2-6x-2)= | | 5b-3=7b+11 | | 4x+10y=35 | | x(5-x)+4(x^1)= | | (5x-6)(4x-7)= | | (5x-7)(3x-2)= | | -7=12-k | | 4d-3=21 | | -32=x-17 | | 237x^2-56x= | | 8x^5y(9x^2+x^2y^3-8y^4)= | | 5a+13=7e-21 | | 3x^2-19x=63 | | 7y-5y=6 | | (4x-5)+(3x-1)= |